1983
DOI: 10.1176/appi.psychotherapy.1983.37.4.552
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Interpersonal Therapy (IPT) with the Depressed Elderly: Case Reports and Discussion

Abstract: Interpersonal psychotherapy (IPT), a short-term treatment developed and tested for use with ambulatory depressed patients, has been successfully applied to elderly patients in a recent pilot study. Case reports of treated elderly patients are presented and the specific utility of IPT for this population is described. The potential of short-term psychotherapies for the treatment of the elderly is discussed and research directions are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…Moreover, patients who received 16 weeks of IPI developed new social skills over the course ofthe subsequent year, whereas medication-only patients did not (14). Subsequent trials have confirmed the efficacy of IPT as a treatment for depressed outpatients generally (15) as well as for specific depressed subpopulations: adolescent (16)(17)(18)(19), geriatric (20)(21)(22)(23)(24), primary care (25,26), and HIV-positive (27,28) patients.…”
Section: Mood Disordersmentioning
confidence: 95%
“…Moreover, patients who received 16 weeks of IPI developed new social skills over the course ofthe subsequent year, whereas medication-only patients did not (14). Subsequent trials have confirmed the efficacy of IPT as a treatment for depressed outpatients generally (15) as well as for specific depressed subpopulations: adolescent (16)(17)(18)(19), geriatric (20)(21)(22)(23)(24), primary care (25,26), and HIV-positive (27,28) patients.…”
Section: Mood Disordersmentioning
confidence: 95%
“…The short-term psychotherapy programme A short-term form of psychotherapy was used (Bennett, 1984;Sholomskas, Chevron, Prusoff & Berry, 1983). Compared with long-term psychotherapy, it is limited in its goals, which consist of improvement of coping, enhancement of self-construing, and expression and recognition of emotions.…”
Section: Methodsmentioning
confidence: 99%
“…Frank et al (1993) developed it as a treatment for late-life depression. Sholomskas et al (1993) state that although IPT is easily applicable with older people, there are three main considerations to take into account. The IPT therapist needs to adopt an active non-neutral stance in therapy.…”
Section: Interpersonal Psychotherapy For Late-life Depressionmentioning
confidence: 99%